Full-endoscopic decompression surgery in the treatment of elderly patients with degenerative lumbar spinal stenosis - Gao, Shangjv; Shi, Lifang; Cao, Can; Wei, Jingchao; Lv, Wenjie; Li, Wenyi (Frontiers in Surgery, 2025)
ObjectiveTo introduce the technical protocol of the full-endoscopic decompression surgery (FEDS) in the treatment of elderly patients with degenerative lumbar spinal stenosis (DLSS) and evaluate its clinical efficacy compared with posterior transforaminal lumbar interbody fusion (PTLIF).MethodsA retrospective study was conducted on 82 elderly patients (aged ≥70 years) with DLSS, including 45 patients who underwent FEDS (FEDS group) and 37 patients who underwent PTLIF (PTLIF group). General data including age, sex, American Society of Anesthesiologists (ASA) classification, surgical segment, preoperative visual analogue scale (VAS) for low back pain and leg pain, and preoperative Oswestry Disability Index (ODI) were compared between the two groups. VAS for low back pain, VAS for leg pain, and ODI were recorded at 6 weeks, 6 months, and the last follow-up after surgery. Operation-related parameters such as operation time and length of hospital stay were recorded. Early and late complications were also compared between the two groups to assess their safety and efficacy.ResultsThe average age of patients in the FEDS group was 75.6 years, older than that in the PTLIF group (74.1 years, P = 0.037). The preoperative VAS for low back pain was lower in the FEDS group compared to the PTLIF group (P = 0.022). There were no significant differences between the two groups in terms of sex, ASA classification, surgical segment, preoperative VAS for leg pain, and preoperative ODI. The follow-up period was 17.0 ± 3.7 months (range 12–30 months). Significant improvements in VAS for low back pain, VAS for leg pain, and ODI were observed during follow-ups compared to preoperative values. The FEDS group had shorter operation time and length of hospital stay compared to the PTLIF group (both P < 0.001). There were no significant differences in early and late complications between the two groups, although the types of complications differed.ConclusionFEDS is as effective as PTLIF in the treatment of elderly patients with DLSS.